Better vaguely right than precisely wrong in effective altruism: the problem of marginalism. (30th March 2023) - Côté, Nicolas; Steuwer, Bastian
Abstract: Effective altruism (EA) requires that when we donate to charity, we maximize the beneficial impact of our donations. While we are in broad sympathy with EA, we raise a practical problem for EA, which is that there is a crucial empirical presupposition implicit in its charity assessment methods which is false in many contexts. This is the presupposition that the magnitude of the benefits (or harms) generated by some charity vary continuously in the scale of the intervention performed. We characterize a wide class of cases where this assumption fails, and then draw out the normative implications of this fact.